QAWAID AL-TAHDIS DALAM TINJAUAN HISTORIS - Ali, Muhammad; Husni, Fajril (Fakultas Ushuluddin dan Filsafat Universitas Islam Negeri Alauddin Makassar, 2023)
This article discusses the history, scope and urgency of Qawaid al-Tahdis. In this article there are several important things that will become the core of the discussion, namely, the definition of Qawaid al-Tahdis, the history of the development and growth of Qawaid al-Tahdis from various perspectives of scholars, the scope of Qawaid al-Tahdis and its urgency. Therefore, it is necessary to explain these things so as not to cause confusion and misunderstanding in understanding related to the history of Qawaid al-Tahdis. The study of this problem was carried out by conducting a literature review with a historical approach. So the conclusion is qawaid al-tahdis is a science that studies related to the rules in hadith scholarship. In its development, qawaid al-tahdis, in the historical aspect, there is a difference of opinion among hadith reviewers regarding the historical development of hadith. The discussion in qawaid al-tahdis includes studies from the aspect of the authenticity of the Prophet's hadith. Qawaid al-tahdis becomes an important science because there are many distortions to the hadith of the Prophet. so that it becomes an analytical knife in the study of hadith.